1992
DOI: 10.1103/physrevb.45.13117
|View full text |Cite
|
Sign up to set email alerts
|

Phase transitions in antiferromagnetic superlattices

Abstract: W'e investigate the temperature dependence of the magnetization of films and superlattices of uniaxial antiferromagnets using a self-consistent, mean-field approach and apply the theory to FeF2/CoF2superlattices. The number of magnetic phase transitions in this system (one or two) depends on the thicknesses of the films in the superlattice and on the interface exchange constant. Weak interface coupling leads to two transitions as do thick films. Our findings are in good agreement with recent experimental resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(38 citation statements)
references
References 18 publications
2
36
0
Order By: Relevance
“…We attribute the observed stable magnetic moment in the -Mn 2 O 3 shell well above T C to the interface exchange coupling between the MnO core and the shell, as has been experimentally and theoretically observed in film systems [16][17][18][19][20][21][22]41,42], that can tentatively be considered as a magnetic proximity effect. Namely, although uncompensated spins may play a role in the proximity effect [12], the exchange field of each sublattice of the AFM core, which penetrates a few atomic layers, stabilizes the magnetic structure of the sublattices of the FIM shell [41,42]. These results are in agreement with the theoretical results in bilayer thin films from Jensen et al who predicted an increase of the temperature range of stable moments to above T C in AFM/FM systems with T N > T C [41].…”
supporting
confidence: 64%
“…We attribute the observed stable magnetic moment in the -Mn 2 O 3 shell well above T C to the interface exchange coupling between the MnO core and the shell, as has been experimentally and theoretically observed in film systems [16][17][18][19][20][21][22]41,42], that can tentatively be considered as a magnetic proximity effect. Namely, although uncompensated spins may play a role in the proximity effect [12], the exchange field of each sublattice of the AFM core, which penetrates a few atomic layers, stabilizes the magnetic structure of the sublattices of the FIM shell [41,42]. These results are in agreement with the theoretical results in bilayer thin films from Jensen et al who predicted an increase of the temperature range of stable moments to above T C in AFM/FM systems with T N > T C [41].…”
supporting
confidence: 64%
“…For free-standing AFM nanocrystals, or AFM nanocrystals embedded in or supported by nonmagnetic matrix, their T N (D) continuously decreases with dropping D due to also the increase of surface/volume ratio as observed in systems of FeF 2 /ZnF 2 [230,231] superlattices, and CoO/SiO 2 [232,233], CoO/MgO [234], NiO/MgO [234,235], Ho/Nb/Y, Ho/Y/Nb [128] thin films, as well as NiO [236], CoO [237] and MnO [238] nanoparticles, and CuO nanoparticles [239][240][241][242], nanorods [242]. Compared with the superlattices of AFM layers with nonmagnetic interlayers [243,244], because of the interlayer magnetic coupling [245][246][247][248], weaker finite size effect for the superlattices of AFM/AFM insulators with exhibiting single transition temperatures have also been observed in the superlattices systems of FeF 2 /CoF 2 [249] and NiO/CoO [250] measured by thermal expansion and magnetic susceptibility, respectively.…”
Section: Size Dependence Of the Néel Temperaturementioning
confidence: 99%
“…The isotropic Heisenberg model does not have long-range order at finite temperature (i.e., c 0 T = ) for the limit of only one layer (two-dimensional lattice -2d) [16], but it is shown theoretically that even a very small amount of anisotropy may lead to magnetic order with a substantial transition temperature [17]. In contrast to the ferromagnetic systems discussed above, antiferromagnetic films have been little studied [18][19][20]. It has been shown that quantum fluctuations can cause unexpected effects at low temperatures in non-homogeneous systems such as, for example, in the frustrated Heisenberg model [21] or antiferromagnetic superlattices [22].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the phase diagram of the three-dimensional HAM in the T-H plane (H is the external magnetic field) was calculated by an effective-field theory (EFT) [35]. The critical behavior of the Néel temperature N ( ) T H as a function of the magnetic field (H) was obtained in the whole interval of H. To our knowledge, few people have studied the surface effects in antiferromagnetic spin models [18][19][20]36]. Motivated by the absence of results on the phase diagram in the T-H plane for a thin quantum spin-1 2 / Heisenberg antiferromagnetic film, we propose in this work to study this system by using EFT.…”
Section: Introductionmentioning
confidence: 99%